2003
DOI: 10.1007/s005350300069
|View full text |Cite
|
Sign up to set email alerts
|

A decreased number of c- kit -expressing cells in a patient with afferent loop syndrome

Abstract: Following gastrectomy, stasis in the afferent jejunal loop accompanied by an overgrowth of bacteria leads to a number of clinical symptoms, including the so-called afferent loop syndrome. The disturbances in intestinal motility may be related to stagnation of the intestinal contents in the afferent loop. The pacemaker cells for the basic contractile activity of the intestine are thought to be the interstitial cells of Cajal (ICCs). We and others have reported that ICCs express the c- kit receptor, and that a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Deficiency of ICC has been demonstrated in various gastrointestinal motility disorders in humans and animals [1][2][3][4][5][6][7][8][9][10][11][12][13][23][24][25], including the above-mentioned motor disorders. ICCs direct the electrical rhythmicity and peristalsis of the gut [26,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiency of ICC has been demonstrated in various gastrointestinal motility disorders in humans and animals [1][2][3][4][5][6][7][8][9][10][11][12][13][23][24][25], including the above-mentioned motor disorders. ICCs direct the electrical rhythmicity and peristalsis of the gut [26,39].…”
Section: Discussionmentioning
confidence: 99%
“…ICC may also play similar roles in other tubular, smooth muscle-lined organs, such as the urethra and lymph vessels, in a wide range of species [2]. Absence of, or a decrease in, ICC has been reported in patients with chronic pseudo-obstruction [3], achalasia of cardia [4], pyloric stenosis [4], colonic inertia [5], afferent loop syndrome [6], internal anal sphincter achalasia [7], Hirschsprung's disease [7], and gut dysmotility associated with diabetes mellitus [8][9][10]. In addition, partial bowel obstruction [11], surgical resection of the gut [12], and jejunal inflammation [13] disrupt ICC networks and cause abnormal motility.…”
Section: Introductionmentioning
confidence: 99%
“…Nonobstructive afferent loop syndrome leads to retrograde cholangitis, liver abscess, and the formation of enterolithiasis or intrahepatic lithiasis, and occurs in around 37% of all of the afferent loop syndrome cases. 1214 It is thought that sump syndrome after hepaticojejunostomy presents the same pathology as nonobstructive afferent loop syndrome. 1517 …”
Section: Discussionmentioning
confidence: 99%
“…However, as Kiyohara et al 20 have noted, there seem to be some issues that should be carefully considered. First, does the lack of detectable KIT immunoreactivity really indicate the loss of ICCs?…”
Section: Alterations Of Interstitial Cells Of Cajal and Gastrointestimentioning
confidence: 99%
“…In this issue of the Journal of Gastroenterology, Kiyohara et al 20 report a decrease in ICCs in a patient with afferent loop syndrome that was observed 39 years after a subtotal gastrectomy with a Billroth II gastrojejunostomy and 26 years after an additional partial Interstitial cells of Cajal (ICCs) in the gastrointestinal (GI) tract were first described by Cajal 1 in 1893 as primitive neurons in autonomically innervated organs. Since then, with the use of light and then electron microscopy, considerable debate about the distribution, origin, and function of ICCs has continued over the years.…”
mentioning
confidence: 99%